Wood Particle Board Manufacture - Ganguly, Dilip. K. (Indian Forester, 1968)
This article has been written by the author on the basis of the experience gained by him in Canada where he obtained special training in this field. The various processes involved in the manufacture of Wood Particle Board by flat platen process have been described. These are debarking of wood, chipping, drying, secondary reduction, adhesive mixing, mat forming, pressing, trimming, sanding and finishing. Each stage has been discussed in detail and the suitabilities of various alternative systems have been analysed.